Uncertainty propagation in inverse reliability-based design of composite structures - António, Carlos Alberto da Conceição António (2009)
Analysis of uncertainty propagation in Reliability-Based Design Optimization (RBDO) of composite laminate structures is presented. Using the Uniform Design Method (UDM) a set of design points is generated over a domain centred on the mean values of the random variables aiming to study the space variability. An approach based on optimal design of composite structures to achieve a specified reliability level is proposed and the corresponding maximum load is outlined as a function of ply angle. Using the generated UDM design points as input/output patterns an Artificial Neural Networks (ANN) is developed. The developed ANN and a Monte Carlo procedure are used to analyse the variance of structural reliability index and their relative sensitivities as a function of ply angle. Numerical examples showing the utility of the approach applied to angle-ply laminates are presented.